Egypt's COVID-19 Recent Happenings and Perspectives: A Mini-Review - Saied, AbdulRahman A.; Metwally, Asmaa A.; Madkhali, Norah Abdullah Bazekh; Haque, Shafiul; Dhama, Kuldeep (Frontiers in Public Health, 2021)
The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus – 2 (SARS-CoV-2), has affected countries across the world. Whilst the zoonotic aspects of SARS-CoV-2 are still under investigation, bats and pangolins are currently cited as the animal origin of the virus. Several types of vaccines against COVID-19 have been developed and are being used in vaccination drives across the world. A number of countries are experiencing second and third waves of the pandemic, which has claimed nearly 4 million lives out of the 180 million people infected globally as of June 2021. The emerging SARS-CoV-2 variants and mutants are posing high public health concerns owing to their rapid transmissibility, higher severity and, in some cases, ability to infect vaccinated people (vaccine break-through). Here in this mini-review, we specifically looked at the efforts and actions of the Egyptian government to slow down and control the COVID-19 spread. We also review the COVID-19 statistics in Egypt and the possible reasons behind the low prevalence and high case fatality rate (CFR %), comparing Egypt COVID-19 statistics with China (the epicenter of COVID-19 pandemic) as well as the USA, Brazil, India, Italy, and France (the first countries in COVID-19 infected patients' numbers). Additionally, we have summarized the SARS-CoV-2 variants, vaccines used in Egypt, and the use of medicinal plants as preventive and curative options.